2019
DOI: 10.1002/solr.201900261
|View full text |Cite
|
Sign up to set email alerts
|

Nickel Oxide Hole‐Selective Heterocontact for Silicon Solar Cells: Role of SiOx Interlayer on Device Performance

Abstract: Carrier‐selective contact‐based silicon heterojunction solar cells are fabricated using nickel oxide (NiOx) as a hole‐selective layer by thermal evaporation. The highest power conversion efficiency of ≈15.20% with a chemically grown SiOx interlayer is achieved from a Ag/ITO/NiOx/n‐Si/LiFx/Al cell structure in comparison with ≈12.43% without SiOx. The cells without and with the SiOx layer are analyzed by considering crucial parameters for conversion efficiency, such as minority carriers' diffusion lengths, life… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
43
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(46 citation statements)
references
References 23 publications
2
43
0
1
Order By: Relevance
“…Even the case with the lowest D it is still over an order of magnitude worse than the performance modeled in the (p) a-Si:H cell. Nayak et al have recently achieved higher performing cells with a NiO x p-layer [22], which is probably due to better passivation and lower D it , but we note that this device architecture does not use an intrinsic a-Si:H layer, so our simulation is not directly transferable here. This corroborates our simulations from Fig.…”
Section: B Case Study: Sputtered P-type Nio X As a Hole-selective Comentioning
confidence: 95%
See 3 more Smart Citations
“…Even the case with the lowest D it is still over an order of magnitude worse than the performance modeled in the (p) a-Si:H cell. Nayak et al have recently achieved higher performing cells with a NiO x p-layer [22], which is probably due to better passivation and lower D it , but we note that this device architecture does not use an intrinsic a-Si:H layer, so our simulation is not directly transferable here. This corroborates our simulations from Fig.…”
Section: B Case Study: Sputtered P-type Nio X As a Hole-selective Comentioning
confidence: 95%
“…However, as shown recently, it is also possible that SiO x is forming at the interface without a significant detrimental effect on passivation [62]. In fact, Nayak et al reported that an intentionally introduced SiO x layer actually improves the solar cell performance in (n) c-Si / (i) SiO x / (p) NiO x devices [22]. The implications for an (n) c-Si / (i) a-Si:H / (i) SiO x / (p) NiO x device remain to be explored.…”
Section: B Case Study: Sputtered P-type Nio X As a Hole-selective Comentioning
confidence: 96%
See 2 more Smart Citations
“…率最高的 HCT 太阳电池。相比 p + :a-Si 发射层的 HJT 电池,其短路电流密度 J SC 提高了 1.3 mA/cm 2 。p 型半导体材料 NiO x [13,14] , Cu 2 O x [15] 的研究较为少见,目前报道的最高效率是印度 理工学院德里分校 Nayak 等人 [13] 以热蒸发 NiO x 为发射极,LiF x 为背场结制备的晶硅异质 结电池,其效率达到 15.20%。南开大学 Yang 等人 [14]…”
unclassified